Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.6 - Rational Expressions - Exercise Set - Page 85: 55


$\displaystyle \frac{-(x^{2}+2x-1)}{(x+1)(x-1)}, \qquad x\neq 1, -1$

Work Step by Step

Factor each denominator. $x^{2}-1=(x+1)(x-1)\qquad $... (a difference of squares) $LCD=(x+1)(x-1)$ $\displaystyle \frac{x+3}{x^{2}-1}-\frac{x+2}{x-1}=\frac{x+3}{(x+1)(x-1)}-\frac{x+2}{x-1}$ $=\displaystyle \frac{x+3}{(x+1)(x-1)}-\frac{x+2}{x-1}\times\frac{x+1}{x+1}$ $=\displaystyle \frac{x+3}{(x+1)(x-1)}-\frac{x^{2}+3x+2}{(x+1)(x-1)}$ $=\displaystyle \frac{x+3-x^{2}-3x-2}{(x+1)(x-1)}$ $=\displaystyle \frac{-x^{2}-2x+1}{(x+1)(x-1)}$ $=\displaystyle \frac{-(x^{2}+2x-1)}{(x+1)(x-1)}, \qquad x\neq 1, -1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.